Kebijakan Energi Uni Eropa Setelah Serangan Rusia ke Ukraina Februari Tahun 2022 - Imaddudin Ahmad Juanda; Hesti Rosdiana (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
The study "European Union Energy Policy After Russia's Attack on Ukraine in February 2022" analyzes the EU's energy policies in response to the energy crisis caused by the attack, which disrupted the EU's heavily Russian-dependent energy supply. Using a qualitative method with a descriptive analytical approach, the research identifies the EU's strategic steps to reduce energy dependence on Russia and transition to sustainable energy. The findings highlight the REPowerEU policy, under Regulation (EU) 2023/435, as the primary response, focusing on diversifying energy imports, increasing renewable energy production, promoting energy efficiency, and enhancing energy infrastructure. Key initiatives include renewable energy projects like solar power in Spain and Portugal, the North Sea Wind Power Hub, and the Celtic Interconnection project, as well as the Renovation Wave Initiative to improve building energy efficiency. These measures aim to address the immediate energy crisis and build a sustainable, resilient energy future for the EU. The study provides academic insights into EU energy policy and security, serving as a reference for those interested in energy policy and international energy security.